2022
DOI: 10.1161/strokeaha.121.036396
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1R/A3R (Adenosine A1 and A3 Receptor) Agonist AST-004 Reduces Brain Infarction in a Nonhuman Primate Model of Stroke

Abstract: Background and Purpose: Treatment with A1R/A3R (adenosine A1 and A3 receptor) agonists in rodent models of acute ischemic stroke results in significantly reduced lesion volume, indicating activation of adenosine A1R or A3R is cerebroprotective. However, dosing and timing required for cerebroprotection has yet to be established, and whether adenosine A1R/A3R activation will lead to cerebroprotection in a gyrencephalic species has yet to be determined. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 50 publications
4
28
0
Order By: Relevance
“…It is possible that a balance of AST-004 A1R and A3R agonism in rats results in significant efficacy, but at high doses, the peripheral cardiovascular effects of A1R agonism reduce this cerebroprotection. Again, this appears to be a rat-specific phenomenon, since we did not observe any evidence of hormesis or blood pressure effects over a broad dose range in a recent primate stroke efficacy study 14 . More research is required to test the role of A1R agonism at higher doses in our stroke models.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…It is possible that a balance of AST-004 A1R and A3R agonism in rats results in significant efficacy, but at high doses, the peripheral cardiovascular effects of A1R agonism reduce this cerebroprotection. Again, this appears to be a rat-specific phenomenon, since we did not observe any evidence of hormesis or blood pressure effects over a broad dose range in a recent primate stroke efficacy study 14 . More research is required to test the role of A1R agonism at higher doses in our stroke models.…”
Section: Discussionmentioning
confidence: 52%
“…Hormesis, or a “U-Shaped” biphasic dose-response has been observed with many CNS-active agents 42,43 . Importantly, no hormesis was observed in primate stroke efficacy studies, in which a clear AST-004 dose- and concentration-related effect was observed on inhibition of stroke lesion growth 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is worth noting that recent findings from basic research highlighted a promising neuroprotective effect exerted by a new compound, a mixed and partial agonist of A 1 Rs and A 3 Rs, known as AST-004 (MRS4322), a low-molecular-weight nucleoside metabolite recently synthetized by the group of Kenneth Jacobson [ 78 ]. Experimental models of stroke performed in mice [ 78 ] or non-human primates [ 79 ] demonstrated that treatment with the A 1 R/A 3 R agonist after acute ischemic stroke resulted in significantly reduced lesion volume, without alterations in cardiovascular parameters. The cerebroprotective effect of the compound was also found to correlate with unbound AST-004 concentrations in the plasma and cerebrospinal fluid, as well as estimated brain A 1 R and A 3 R occupancy, indicating the activation of adenosine A 1 Rs and/or A 3 Rs [ 79 ].…”
Section: Therapeutic Potential Of a 3 R Ligandsmentioning
confidence: 99%
“…Experimental models of stroke performed in mice [ 78 ] or non-human primates [ 79 ] demonstrated that treatment with the A 1 R/A 3 R agonist after acute ischemic stroke resulted in significantly reduced lesion volume, without alterations in cardiovascular parameters. The cerebroprotective effect of the compound was also found to correlate with unbound AST-004 concentrations in the plasma and cerebrospinal fluid, as well as estimated brain A 1 R and A 3 R occupancy, indicating the activation of adenosine A 1 Rs and/or A 3 Rs [ 79 ]. Such encouraging data prompted the evaluation of AST-004 in a Phase I clinical trial for stroke ( ; 12 March 2022).…”
Section: Therapeutic Potential Of a 3 R Ligandsmentioning
confidence: 99%